Preparation of pH / gsh dual-responsive tri-block copolymer with aie luminescence and its application as drug carrier
Patent Information
- Application Number
- CN202310680402.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2043-06-09
AI Technical Summary
然而传统的荧光染料存在聚集诱导猝灭(ACQ)效应,有机荧光团很容易在聚集态下发生猝灭导致荧光强度下降,影响检测和监测效果
[0040] In summary, this invention utilizes RAFT living polymerization to prepare an amphiphilic triblock polymer SS-GMDP with three disulfide bonds on its side chains, introducing the fluorescent molecule DPME with AIE (Active Injection) properties into the side chains. Then, the drug molecule CPT was successfully encapsulated in PBS medium via self-assembly, yielding polymer nanoparticles SS-GMDP-CPT NPs. SS-GMDP emits orange-red fluorescence near 498 nm, with a fluorescence quantum yield of approximately 12.7% and a fluorescence lifetime of 11.28 ns. Furthermore, SS-GMDP exhibits significant AIE properties in unsuitable solvents, with fluorescence intensity increasing significantly with increasing unsuitable solvent concentration. Simultaneously, the average particle size of the polymer prepared as blank micelles and drug-loaded micelles was 105.71 ± 2.46 nm, while the micelle size increased to 128.53 ± 5.09 nm upon addition of the drug molecule camptothecin (CPT). Moreover, the micelles respond rapidly in high-concentration GSH and acidic environments, opening new possibilities for multifunctional drug delivery systems. Then, in vitro release tests were conducted on the drug-loaded micelles in a simulated tumor environment. The results showed that optimal drug release was achieved under acidic conditions and in the presence of GSH, with a cumulative release of 77.2% over 72 hours. Finally, biological experiments demonstrated that the blank micelles SS-GMDP NPs exhibited low cytotoxicity and good biocompatibility. Compared to the free drug molecule CPT, the drug-loaded micelles SS-GMDP-CPT NPs showed a higher cancer cell mortality rate and a lower hemolysis rate. These test results indicate that this material holds promise as a potential drug delivery carrier.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a pH / GSH dual-responsive triblock copolymer with AIE luminescence properties, and also to its application as a drug carrier, belonging to the fields of compound synthesis and drug carrier technology. Background Technology
[0002] Self-assembly of amphiphilic molecules is a simple strategy for constructing functional polymer carriers. For synthesized amphiphilic polymers, the molecular structure controls the assembly process. Polymers have been extensively studied as drug carriers and are gradually being applied clinically. Polymer carriers have the following advantages in drug delivery: high stability, ease of modification, strong loading capacity, excellent degradability, and biosafety. Studies have shown that the concentration of GSH in tumors is approximately 2–10 mM, several times higher than that in normal cells. Therefore, using GSH as a stimulating target for nanomedicine delivery systems is an effective strategy. In addition, fluorescence imaging provides visualization for in vivo or in vitro detection and has important applications in tumor treatment. However, traditional fluorescent dyes suffer from aggregation-induced quenching (ACQ) effects. Organic fluorophores are easily quenched in the aggregated state, leading to a decrease in fluorescence intensity and affecting detection and monitoring results. In 2001, Academician Tang Benzhong's research group first proposed the concept of aggregation-induced emission (AIE). Unlike traditional fluorescent dyes, AIE is characterized by no emission or very weak emission in dilute solutions or non-aggregated states, but significantly enhanced fluorescence in aggregated or solid states. After twenty years of development, AIE has sprung up and been applied in various disciplines and fields, such as bioluminescent probes, organic light-emitting diodes, and bioimaging.
[0003] Currently, AIE molecules have also been used to track and evaluate the imaging and release of nanomedicines in vivo. Researchers have combined AIE fluorescent probes with stimulus-responsive amphiphilic copolymers to prepare a variety of multifunctional nanomedicine carriers with AIE luminescence properties, playing an important role in tumor diagnosis and treatment. For example, AIE polymer micelles with biofluorescence imaging capabilities can visualize the distribution and release of drugs in vivo, thus enabling the evaluation of drug antitumor efficacy. Furthermore, redox-sensitive polymer micelles with AIE properties can be used for intelligent drug delivery and bioimaging, while the AIE groups within the micelle core endow these micelles with unique bioimaging capabilities. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing a pH / GSH dual-responsive triblock copolymer with AIE luminescence properties; Another object of the present invention is to provide the use of the copolymer as a drug carrier.
[0005] To endow SS-GPC-ME NPs drug carriers with excellent fluorescence tracking and responsiveness, we designed and synthesized multi-site responsive polymer nanomicelles based on disulfide bonds and containing AIE luminescent groups in their side chains. First, a vinyl monomer DPME containing disulfide bonds and exhibiting AIE luminescence properties was prepared. Then, using RAFT living polymerization technology, a macromolecule SS-GPC-ME with terminal disulfide esters was used as a chain transfer agent to synthesize a multi-site responsive amphiphilic triblock copolymer SS-GMDP based on disulfide bonds. The introduction of DPME luminescent groups endows the drug delivery system with excellent AIE optical properties, thereby realizing the therapeutic integration function of this type of dual-responsive drug delivery nanomicelle. SS-GMDP exhibits strong self-assembly ability, with a CMC of 0.016 mg / mL. Optical testing results show that the fluorescence emission peak of SS-GMDP is located near 500 nm, exhibiting typical AIE luminescence characteristics, a fluorescence quantum yield of 12.7%, and a fluorescence lifetime of 11.28 ns. Subsequently, the hydrophobic drug molecule camptothecin (CPT) was successfully loaded through self-assembly. Drug release capacity testing results showed that the drug-loaded micelles exhibited excellent pH / GSH dual-response performance. Under weak acidity and in the presence of GSH, the original structure of the drug-loaded nanomicelles was disrupted, and the internal CPT was effectively released. Cytotoxicity experiments showed that, compared with free CPT, SS-GMDP drug-loaded nanomicelles had a higher cancer cell mortality rate and a lower hemolysis rate. Therefore, SS-GMDP drug-loaded nanomicelles with AIE properties hold promise as a potential therapeutic drug delivery carrier.
[0006] I. Preparation of pH / GSH dual-responsive triblock copolymers with AIE luminescence properties 1. Preparation of triblock copolymers (1) Synthesis of 2-(4-bromophenyl)-3-(4-(diphenylamino)phenyl)acrylonitrile (CDPBr) 4-N,N-diphenylaminobenzaldehyde was dissolved in anhydrous ethanol, and p-bromophenylacetonitrile and NaOH were added. The mixture was stirred at room temperature for 2–4 hours under a nitrogen atmosphere. After the reaction was complete, the product was recrystallized from anhydrous ethanol and dried under vacuum to obtain a yellow solid powder, CDPBr. The molar ratio of 4-N,N-diphenylaminobenzaldehyde to p-bromophenylacetonitrile was 1:1 to 1:5; the molar ratio of p-bromophenylacetonitrile to NaOH was 1:1 to 1:2.
[0007] (2) Synthesis of 3-(4-(diphenylamino)phenyl-2-(4-pyridine-phenyl)acrylonitrile (CDPP) CDPBr, pyridine-4-boronic acid, K₂CO₃, and tetrakis(triphenylphosphine)palladium were added to a mixture of THF and deionized water. The mixture was refluxed at 60–80 °C for 24 h under N₂ atmosphere. After cooling to room temperature, it was extracted three times with DCM. The organic phase was collected, washed with deionized water, dried overnight with anhydrous MgSO₄, and the solvent was removed by rotary evaporation. The solution was purified by silica gel column chromatography and vacuum dried to obtain an orange-yellow powder, CDPP. The molar ratio of CDPBr to pyridine-4-boronic acid was 1:1–1:1.5; the molar ratio of CDPBr to K₂CO₃ was 1:10–1:11; and the molar ratio of tetrakis(triphenylphosphine)palladium to CDPBr was 1:222. (3) Synthesis of 3-(4-(diphenylaminophenyl)-2-(4-(1-(2-hydroxyethyl)-1,1,4-pyridin-4-yl)phenyl)acrylonitrile (CDOH) CDPP was dissolved in chloroform, and 2-iodoethanol was added. The mixture was stirred at room temperature under a nitrogen atmosphere for 70–75 h. The solution was extracted three times with saturated brine, dried over anhydrous MgSO4, and the solvent was removed by rotary evaporation. The solution was purified by silica gel column chromatography and dried under vacuum to obtain a red solid, CDOH. The molar ratio of CDPP to 2-iodoethanol was 1:1 to 1:1.5.
[0008] (4) Synthesis of 4-(4-(1-cyano-2-(4-(diphenylamino)phenyl)vinyl)phenyl)-1-(17-methyl-3,3,54,7,16-trioxo-3,8,15-trioxa-11,12-dithiooctadec-17-en-1-yl)pyridine (DPME) CDOH, 4-(2-(2-(methacryloyloxy)ethyldithioalkylethoxy)-4-oxobutyric acid (SS-COOH), dicyclohexylcarbodiimide (DCC), and 4-dimethylaminopyridine (DMAP) were dissolved in anhydrous DCM. The mixture was stirred at room temperature under N2 atmosphere for 20–25 h. After the reaction was complete, the mixture was filtered to remove impurities, the solvent was removed by rotary evaporation, and the mixture was purified by silica gel column chromatography to obtain red solid DPME. The molar ratio of CDOH to SS-COOH was 1:1 to 1:1.5; the molar ratio of CDOH to dicyclohexylcarbodiimide was 1:1.2 to 1:1.6; and the molar ratio of 4-dimethylaminopyridine to CDOH was 1:8 to 1:10.
[0009] (5) Synthesis of 2-(hydroxymethyl)-17-methyl-4,7,16-trioxy-11,12-dithiooctadecyl-17-en-1-yl (2-(trimethylamino)ethyl) phosphate (SS-GPC) SS-COOH was dissolved in DCM, and N,N'-carbonyldiimidazole was added with stirring at room temperature. Glyceryl phosphate choline and 1,8-diazabicyclo[5.4.0]undec-7-ene were dissolved in dimethyl sulfoxide. The mixture was stirred at 55-65°C for 3-5 h until completely dissolved. After cooling to room temperature, the two solutions were mixed and stirred at room temperature for 20-25 h. The mixture was purified by silica gel column chromatography and freeze-dried to obtain a white solid SS-GPC. The molar ratio of SS-COOH to N,N'-carbonyldiimidazole was 1:1 to 1:2; the molar ratio of glyceryl phosphate choline to 1,8-diazabicyclo[5.4.0]undec-7-ene was 1:1 to 1:2; and the molar ratio of N,N'-carbonyldiimidazole to 1,8-diazabicyclo[5.4.0]undec-7-ene was 2:1 to 3:1.
[0010] (6) Synthesis of 2-(azacyclopropane)-1-ethyl(2-((2-(methacryloyloxy)ethyl)dithioyl)succinate (SS-ME) Weigh SS-COOH, N-(2-hydroxyethyl)hexamethylenediamine, 4-dimethylaminopyridine, and dicyclohexylcarbodiimide and dissolve them in DCM. Stir at room temperature for 20-25 h. After the reaction is complete, extract with saturated sodium chloride solution, dry with anhydrous MgSO4, remove the solvent by evaporation and rotation, and purify by silica gel column chromatography to obtain SS-ME. The molar ratio of SS-COOH to N-(2-hydroxyethyl)hexamethylenediamine is 1:1 to 1:2; the molar ratio of N-(2-hydroxyethyl)hexamethylenediamine to 4-dimethylaminopyridine is 1:1 to 1:2; and the molar ratio of N-(2-hydroxyethyl)hexamethylenediamine to dicyclohexylcarbodiimide is 8:1 to 12:1.
[0011] (7) Preparation of polymer SS-GMDP Chain transfer agent 3-((phenylthio)carbonylthio)propionic acid (CADB), initiator azobisisobutyronitrile (AIBN), and SS-GPC were dissolved in DMF solution and stirred for 10-15 h at 75-85 °C under N2 atmosphere. SS-ME was added and the reaction continued for another 10-15 h. Subsequently, DPME was added, and after cooling to room temperature, methyl tert-butyl ether precipitated. The precipitate was washed with acetone solution, dialyzed against deionized water at room temperature, and freeze-dried to obtain polymer SS-GMDP. The molar ratios of CADB to DPME were 1:18-1:22; AIBN to DPME were 1:1-1:2; DPME to SS-GPC were 1:8-1:12; and DPME to SS-ME were 1:8-1:12. The synthetic route of the polymer is as follows: Figure 1 .
[0012] 2. Preparation of polymer-loaded drug micelles The triblock polymer SS-GMDP and the drug molecule camptothecin were dissolved in DMSO solution and stirred at room temperature for 2–4 h. Deionized water was then added, and stirring continued for 20–25 h. The mixture was dialyzed with ultrapure water, and the final solution was freeze-dried to obtain drug-loaded micelles SS-GMDP-CPT NPs. Blank micelles were prepared using the same method to obtain blank micelles SS-GMDPNPs. A schematic diagram of the self-assembly process and drug release of SS-GMDP-CPT NPs is shown below. Figure 2 .
[0013] II. Structure and Properties of Polymers 1. Infrared spectral characterization of polymers The polymer was characterized using infrared spectroscopy via potassium bromide pelleting. For example... Figure 12 As shown, for the triblock polymer SS-GMDP, after adding DPME molecules for RAFT polymerization, at 1725 cm⁻¹... -1 A characteristic peak of C=O stretching vibration appears at 1100 cm⁻¹. -1 A -CS stretching vibration peak appeared at 515 cm⁻¹. -1 The presence of the characteristic peak of SS stretching vibration indicates that the DPME luminescent group was successfully introduced into the diblock polymer SS-GPC-ME.
[0014] 2. Gel permeation chromatography (GPC) test of polymers Polymers used as drug-carrying micelles have molecular weight as a key factor affecting drug delivery. The molecular weight of the triblock polymer SS-GMDP was determined using gel permeation chromatography (GPC), with chromatographically pure DMF as the mobile phase and polystyrene as the standard. The test results are as follows: Figure 13 As shown, the number-average molecular weight (M) of the triblock polymer SS-GMDP is... n The weight-average molecular weight (M) is 12353. w The measured relative molecular weight was 13280, PDI = 1.12, which is close to the theoretical value. Furthermore, the single-peak molecular elution curve indicates low impurity levels in the sample, suggesting high purity of the triblock polymer SS-GMDP. 3. AIE properties of polymers Triphenylamine is a fluorescent small molecule with typical AIE (Alternating Induction Emission) properties. When triphenylamine molecules are in an aggregated state, their unique fluorescence characteristics result from restricted intramolecular rotation. Therefore, DPME containing a triphenylamine structure and the polymer SS-GMDP also exhibit AIE properties.
[0015] (1) AIE effect in different solvents To verify the AIE properties of DPME and the polymer SS-GMDP, we selected EtOH, ACN, DMF, DCM, DMSO, THF, MeOH, and H2O as solvents to study the solvent effect of DPME and the polymer. The excitation wavelength of SS-GMDP was 410 nm, and that of DPME was 400 nm. The polymers were dissolved in different solvents while maintaining a concentration of 1 mmol / mL. Figure 14 As shown in Figure (a), the strongest fluorescence emission peak appears at 482 nm when different solvents are added. In contrast, in Figure (b), DPME reaches its maximum fluorescence intensity at 633 nm. The fluorescence intensity of SS-GMDP and DPME changes with the solvent. For example, the fluorescence intensity of the polymer in DMF is only 248, the lowest, while in EtOH, its fluorescence intensity is 1320. Furthermore, compared to DPME, the fluorescence of polymer SS-GMDP shows a significant blue shift. The main reason for this phenomenon is that DPME molecules are in a relaxed state in good solvents, giving them ample space for movement. However, after polymerization, the interaction between polymer chains restricts the free movement of DPME molecules to some extent. Simultaneously, the limited space makes it difficult for DPME molecules to vibrate, allowing some energy to be retained, resulting in a blue shift in the fluorescence of polymer SS-GMDP. Additionally, the overlapping of polymer chains may also hinder non-radiative transitions, leading to a blue shift in fluorescence emission.
[0016] (2) AIE effect in poor solvents The AIE fluorescent group containing a triphenylamine structure exhibits restricted intramolecular rotation in its aggregated state, resulting in unique fluorescence properties. We first selected Ac as a good solvent for DPME and H₂O as a poor solvent, and DMSO as a good solvent for SS-GMDP and H₂O as a poor solvent, preparing Ac / H₂O and DMSO / H₂O mixed solutions with different ratios. Under the same conditions, we tested the luminescence behavior of DPME and SS-GMDP. Figure 15 As shown in (a), the fluorescence intensity of DPME and SS-GMDP increased significantly with the addition of the undesirable solvent, and the peak fluorescence intensity of SS-GMDP at 482 nm continued to increase with the addition of the undesirable solvent H2O. Figure 15As shown in (b), the fluorescence exhibits a non-linear enhancement trend when the volume fraction of the undesirable solvent H2O increases from 10% to 90%. This is mainly due to the addition of the undesirable solvent, which reduces the solubility of SS-GMDP, induces the formation of aggregates, and produces an AIE phenomenon, thus leading to enhanced fluorescence. The insets show fluorescence comparison photographs of solutions with 10% and 90% undesirable solvent content under 365 nm UV light irradiation. The figures clearly show that the fluorescence brightness of the solution with 90% undesirable solvent is much stronger than that of the solution with 10%, further demonstrating the AIE performance of SS-GMDP in its aggregated state, which will endow the drug-loaded nanomicelles with excellent fluorescence tracing capabilities in vivo.
[0017] (3) AIE effect at different concentrations To further verify the AIE luminescence properties of DPME and the polymer SS-GMDP, we investigated the fluorescence intensity trends of DPME and SS-GMDP at different concentrations. Figure 16 As shown, the fluorescence intensity of DPME and SS-GMDP solutions increases with increasing concentration. This is attributed to the fact that the aggregation degree of the luminescent chromophores increases with increasing concentration, thereby causing fluorescence enhancement. The results demonstrate that both DPME and the polymer SS-GMDP have typical AIE characteristics.
[0018] (4) AIE effect under different pH conditions To evaluate the potential applications of SS-GMDP and DPME in bioimaging, we investigated the effect of pH on their fluorescence intensity. Figure 17 The fluorescence spectra and trends of SS-GMDP and DPME under different pH conditions are shown in the figure. As can be seen, SS-GMDP exhibits the highest fluorescence intensity at pH 5.0, gradually decreasing in alkaline environments (pH 7.0–10.0). This phenomenon is attributed to the varying concentrations of hydrogen ions in solutions at different pH levels. Hydrogen ions coordinate with iodide ions on the pyridine group, removing the negatively charged iodide ion and exposing a positron to the pyridine group, thus increasing its rigidity and consequently enhancing fluorescence intensity. However, at pH values above 7.0, an alkaline environment is present, causing the pyridine group to coordinate with the negatively charged hydroxyl group, leading to a decrease in fluorescence intensity. Most cells generally have a near-neutral pH, while tumor cells are slightly acidic, suggesting that SS-GMDP has significant potential for bioimaging applications.
[0019] (5) GSH responsiveness of polymers In normal cells, the concentration of GSH ranges from 0.5 to 2 mM, while tumor cells contain excessively high concentrations of GSH, averaging as high as 10 mM. To verify whether the fluorescent groups in the polymer chain are responsive to GSH, the fluorescence of the polymer SS-GMDP was tested by adding different concentrations of GSH. Figure 18 As shown, after co-incubation with SS-GMDP for 4 h with GSH, the fluorescence intensity at 498 nm showed a slight change. After adding 10 mM GSH, the fluorescence at 498 nm red-shifted, and the fluorescence intensity at 532 nm significantly increased. The fluorescence intensity of SS-GMDP also increased with increasing GSH concentration. The unique reactivity of the fluorophore to GSH indicates that the pyridinium moiety plays a role in GSH recognition. GSH exists mainly in solution as a thiolate, exhibiting strong nucleophilicity. This phenomenon is due to the electrostatic interaction between the cationic pyridinium salt and biothiols. This electrostatic interaction accelerates the reaction rate of GSH to pyridinium attack, forming a complex with the pyridinium salt, leading to increased fluorescence intensity. This demonstrates that SS-GMDP has a good responsiveness to GSH, indicating that SS-GMDP can be well applied in tumor cells, providing a new method and means for cell imaging.
[0020] (6) Fluorescence stability of the polymer The fluorescence stability of polymers is an important parameter in practical applications. For example... Figure 19 As shown, after 7 and 14 days of immersion in DMSO solution, the fluorescence intensity of the polymer decreased from 900 to 790, a relatively small decrease, demonstrating that the polymer maintains good fluorescence stability. Furthermore, the polymer's fluorescence stability during in vivo circulation can provide good results for tumor site detection and imaging. In addition, the photostability of SS-GMDP under irradiation at different times was investigated. First, concentrated SS-GMDP solution was added to glass slides, and these slides were observed under a fluorescence microscope. The test results are shown below. Figure 19 As shown in (b), the luminescence intensity did not decrease significantly after 24 hours of irradiation. These test results indicate that SS-GMDP has excellent photostability.
[0021] (7) Fluorescence quantum yield and fluorescence lifetime of the polymer Fluorescence quantum yield and fluorescence lifetime are important parameters for evaluating fluorescent substances. We determined the fluorescence quantum yield of SS-GMDP using a reference method, selecting quinine sulfate aqueous solution as the reference for fluorescence emission; its fluorescence quantum yield in aqueous solution was 55%. Figure 20 As shown in Table 1, the fluorescence quantum yield of SS-GMDP is 12.7%. The high fluorescence quantum yield of SS-GMDP indicates that it is advantageous for bioimaging.
[0022] Fluorescence lifetime was determined using single-photon counting. The excitation beam was a portable diode laser (EPL-375, Edinburgh Instruments), which was directed into the sample, and the fluorescence at the corresponding maximum emission value was detected. Both excitation and emission bandwidths were less than 2 nm. Fluorescence lifetime was calculated using the formula: Where B1, B2, and B3 are constants, τ is time, and τ1, τ2, and τ3 are fitted lifetimes. The calculated average fluorescence lifetime of SS-GMDP is 11.28 ns.
[0023] III. Structure and Properties of Polymer Drug-Loaded Micelles 1. Particle size analysis of polymer drug-loaded micelles and blank micelles Freeze-dried drug-loaded polymer micelles SS-GMDP-CPT NPs and blank micelles SS-GMDP NPs were reconstituted with PBS buffer at pH 7.4. The particle size changes before and after drug loading were analyzed using a dynamic light scattering particle size analyzer (DLS). The results are as follows: Figure 21 As shown, the particle size of the blank micelles without drug coating was 105.71±2.46 nm, while the particle size increased to 128.53±5.09 nm after the addition of the drug molecule camptothecin (CPT). The significant change in particle size between the two measurements proves that the drug molecule has been successfully coated inside the polymer carrier.
[0024] 2. Morphological characterization of polymer-loaded drug micelles and blank micelles The morphology of drug-loaded micelles SS-GMDP-CPT NPs and blank micelles SS-GMDP NPs was characterized using SEM and TEM techniques. The results are as follows: Figure 22 As shown, in PBS buffer, the drug-loaded micelles are similar to the blank micelle nanoparticles, with a near-spherical morphology. The average particle sizes are 107.28±2.02 nm and 124.61±6.14 nm, respectively. The average particle size of the drug-loaded micelles is slightly larger than that of the blank micelles, which is because the drug particles are loaded in the micelles, further demonstrating that the polymer carrier can effectively transport drug molecules.
[0025] To further determine the elements contained in the drug-loaded micelles, we performed EDS energy dispersive spectroscopy. Figure 23This is a surface scan of the EDS energy spectrum of the blank micelles formed by SS-GMDP. The color image of the elemental distribution clearly shows that the drug-loaded micelles contain C, N, O, S, and P elements, accounting for 27.96%, 7.19%, 55.31%, 5.97%, and 3.57% respectively. This result further proves that the polymer micelles have been successfully prepared.
[0026] 3. Critical micelle concentration of polymer-loaded drug micelles Critical micelle concentration (CMC) is a crucial parameter for determining whether a polymer can form micelles. When the polymer concentration is too low, below the CMC value, the polymer mostly exists in a dispersed state suspended in the solution. Only when the CMC value is higher will the polymer self-assemble into micelles. Therefore, we use pyrene as a fluorescent probe to detect the formation of micelles by means of I... 365 / I 384 The ratio of the fluorescence intensities at the two locations is used as the ordinate, and the concentration of the polymer sample (lgC) is used as the abscissa, such as... Figure 24 As shown in (a), the fluorescence intensity decreases as the concentration of polymer SS-GMDP decreases. As shown in Figure (b), the fluorescence intensity at 365 nm and 384 nm is compared, and the intersection of the two straight lines is the CMC, which is calculated to be 0.016 mg / mL. This indicates that the polymer can still self-assemble into micelles at low concentrations, and the micelles can maintain good stability.
[0027] 5. Stability test of polymer drug-loaded micelles and blank micelles To verify the stability of the polymer micelles, drug-loaded micelles SS-GMDP-CPT NPs and blank micelles SS-GMDPNPs were placed in PBS buffer at pH 7.4, completely dissolved, and incubated in the dark for 72 h. The micelle size was then measured by DLS. Figure 25 As shown in (a), the drug-loaded micelles SS-GMDP-CPT NPs exhibit good stability in PBS buffer solution at pH 7.4, with an average particle size of 120.76 ± 4.25 nm. After 72 h, the average particle size increased to 128.84 ± 5.04 nm. As shown in Figure (b), the average particle size of the blank micelles SS-GMDP NPs was 105.28 ± 5.62 nm, and after 72 h, the average particle size increased to 110.70 ± 3.11 nm. The particle size of the micelles did not change significantly, indicating that the polymer micelles have good stability.
[0028] When the environment of micelles changes from neutral to acidic conditions, the particle size of the micelles begins to change, such as... Figure 26As shown in (a, b), when the pH is 6.0, the average particle size of the blank micelles increases to 152.81±10.04 nm, and the average particle size of the drug-loaded micelles increases to 158.37±9.86 nm. The changes in micelle size are significant, indicating that the polymer micelles have good acid responsiveness and can be well applied to tumor treatment.
[0029] 6. Standard Curve A certain amount of CPT was dissolved in DMSO solution to prepare a CPT standard solution of 0.0001~0.0005 mg / mL. The solution was then scanned using a UV-Vis spectrophotometer in the wavelength range of 200~600 nm. Figure 27 As shown in (a), the drug molecule CPT exhibits an ultraviolet absorption peak at 275 nm, therefore 275 nm was chosen as its detection wavelength. The blank micelles showed two sets of ultraviolet absorption peaks at 290 nm and 390 nm, while the drug-loaded micelles showed ultraviolet absorption peaks at 275 nm, 290 nm, and 384 nm, demonstrating that the drug-loaded micelles successfully loaded the drug molecule CPT. The absorbance of the prepared standard solution was measured using a UV-Vis spectrophotometer, with DMSO as a control. A standard curve was plotted with absorbance as the ordinate and CPT concentration as the abscissa. Linear regression yielded the equation y = 0.00628x + 0.015805 (R²). 2 =0.9988), indicating that the concentration of CPT standard solution has a good linear relationship with absorbance value.
[0030] 7. Drug Loading Capacity (DLC) and Encapsulation Efficiency (DLE) Polymer drug-loaded micelles prepared using the RAFT polymerization method can have their molecular weight well controlled by adjusting the chain segment ratio. Different chain segment ratios have a certain impact on the DLC and DLE of the drug-loaded micelles, such as... Figure 28 As shown in Table 2, when the ratio of the three polymer side chains is 1:1:10, the DLC and DLE are 15.41% and 61.60% respectively, which is the best drug loading effect. Therefore, this feed ratio is used to prepare the triblock polymer SS-GMDP.
[0031] To further investigate whether different qualities of polymer SS-GPME have an impact on DLC and DLE ( Figure 29Drug-loaded micelles were prepared by adding 5 mg of the drug molecule CPT and weighing 5-50 mg of polymer SS-GPME. The micelles were reconstituted with 5 mL of PBS (pH=7.4), sonicated for 15 min to disrupt the micelle structure, and centrifuged at 8000 rpm for 10 min. After centrifugation, a suitable amount of supernatant was collected, and the absorbance at 275 nm was measured using a UV spectrophotometer. The test results are shown in Table 3. With increasing polymer mass, the drug loading efficiency (DLE) increased, but the drug loading capacity (DLC) did not increase. When 5 mg of polymer SS-GMDP was added, the DLC and DLE were 12.28%. When 30 mg of SS-GMDP was added, the DLC and DLE were optimal at 13.33% and 60.25%, respectively. When 50 mg of SS-GMDP was added, the DLC and DLE were 7.44% and 74.4%, respectively. This demonstrates that with increasing polymer mass, the drug loading efficiency gradually increases, and the mass of the encapsulated drug molecules also increases.
[0032] 8. In vitro release properties of polymer-loaded drug micelles The in vitro release of drug-loaded micelles SS-GMDP-CPT NPs was tested under different environments. First, the drug-loaded micelles were placed in PBS buffers at pH 6.0, pH 7.4, pH 6.0 + 10 mM GSH, and pH 7.4 + 10 mM GSH to simulate the cellular environment for in vitro release experiments. The absorbance at 275 nm was measured using a UV-Vis spectrophotometer. Figure 30As shown, when the pH of the external environment for drug-loaded micelles SS-GMDP-CPT NPs was 7.4, drug release was slow in the first 12 hours, with CPT release reaching only 21.3%. After 72 hours of incubation, CPT release was 25.2%, indicating poor drug release. Drug-loaded micelles are stable before reaching the tumor site, which helps reduce drug leakage during blood circulation and minimizes side effects on the organism. However, when drug-loaded micelles SS-GMDP-CPT NPs were placed in PBS buffer at pH 6.0, the cumulative CPT release in the first 12 hours was 39.9%, significantly higher than that in PBS buffer at pH 7.4. After another 72 hours of incubation, CPT release reached a maximum of 43.0%, indicating that acidic conditions have a certain impact on the polymer drug-loaded micelles SS-GMDP-CPT NPs. The addition of GSH significantly improved the drug release rate. Under conditions of pH 7.4 + 10 mM GSH, the cumulative release of SS-GMDP-CPT NPs reached 68.6% within the first 12 hours and 71.3% at 72 hours. To verify the release effect of SS-GMDP-CPT NPs in a tumor-reducing environment, under conditions of pH 6.0 + 10 mM GSH, the drug release rate was significantly accelerated in the first 12 hours, with a release rate of 72.8% and a cumulative release rate of 77.2% at 72 hours. This result indicates that under acidic conditions and excessively high GSH concentrations, SS-GPC-ME-DOX NPs can achieve slow drug release, encapsulate drug molecules for delivery, and have application value in drug delivery systems.
[0033] Figure 31The particle size changes of drug-loaded micelles SS-GMDP-CPT NPs over 72 h were observed at pH 6.0, pH 6.0 + 10 mM GSH, pH 7.4, and pH 7.4 + 10 mM GSH. As shown in Figure (a), the micelles exhibited a stable overall trend in the PBS solution at pH 7.4, with no significant change in particle size. This is likely due to the folding and stacking of polymer chains after self-assembly of the amphiphilic polymer in solution, with the exposed hydrophobic shell providing excellent anti-interference capabilities and ensuring the stability of the micelles in cell assays. However, in the PBS buffer at pH 6.0, the particle size of SS-GMDP-CPT NPs increased significantly. As shown in Figures (c, d), the drug-loaded micelles SS-GMDP-CPT NPs showed a strong response to 10 mM GSH; the overall particle size increased rapidly after the addition of 10 mM GSH. Furthermore, the size of the micelles increases more rapidly with the rapid change in size distribution from unimodal to multimodal, indicating that GSH disrupts the stable structure of SS-GMDP-CPT NPs, and the breakage of disulfide bonds leads to increased particle size. Experimental results show that the disruption of drug-loaded micelles is most pronounced under acidic conditions and with the addition of GSH, and the polymer-loaded drug micelles exhibit excellent release performance. Therefore, the drug release behavior of SS-GMDP-CPT NPs demonstrates that the drug-loaded micelles possess good stability during blood circulation, enabling accurate drug release into tumor cells, thereby reducing side effects and enhancing anti-tumor efficacy.
[0034] Figure 32 The image shows SEM images of SS-GMDP-CPT NPs incubated for 72 h after the addition of 10 mM GSH. The morphology of the drug-loaded micelles changed under the two environments, transforming from uniform spheres to random nanoparticles. This demonstrates that in the presence of GSH, disulfide bonds break, altering the stable structure of the micelles and leading to the morphological change. These results indicate that within tumor cells, drug-loaded micelles SS-GMDP-CPT NPs can effectively load and release drugs, directly acting on the lesion site to produce a good anti-tumor effect.
[0035] 9. Hemolysis test The biocompatibility of drug-loaded micelles SS-GMDP-CPT NPs was evaluated using a hemolysis assay, such as... Figure 33 As shown, no hemolytic properties were observed in any of the samples. The hemolytic effect tended to decrease slightly with increasing sample concentration, but all were less than 5% of the hemolysis standard. Therefore, the sample has good blood compatibility and can be well transported in vivo.
[0036] IV. Cellular Experiments with Polymers 1. Cytotoxicity Biocompatibility and low toxicity are crucial for the clinical application of drug delivery polymer materials; therefore, we conducted cytotoxicity studies on blank micelles and drug-loaded micelles. The vectors were incubated with HeLa cells and MKN-45 cells for 24 h using the MTT assay, and cell viability was tested. Figure 34 As shown, the cell survival rate was higher than 90% in the concentration range of 10~200 μg / mL. The test results showed that the blank micelles were almost non-toxic, and the prepared multi-block copolymer micelles had good biocompatibility and could be used as potential drug carriers.
[0037] Figure 35 To test the cytotoxicity of drug-loaded micelles SS-GMDP-CPT NPs and free CPT, CPT was loaded into the cells at concentrations ranging from 10 to 200 μg / mL and incubated in a cell culture incubator for 24 h. SS-GMDP-CPT NPs exhibited high cytotoxicity, with cell viability decreasing with increasing concentration. Their cell viability was slightly lower than that of the CPT test group, demonstrating that the drug-loaded micelles have a good inhibitory effect on tumor cell proliferation. The drug-loaded micelles exhibit high toxicity during rapid drug release, killing cancer cells and allowing the drug to reach the lesion site for targeted treatment. The test results indicate that the triblock polymer SS-GMDP shows promise as a potential drug delivery carrier for cancer treatment.
[0038] 2. Cell imaging Because the triblock polymer SS-GMDP has AIE luminescent groups DPME on its side chains, and the drug molecule CPT emits blue light, the fluorescence changes of both can be used to monitor the cellular uptake of micelles and the drug release process within the cells in real time. We observed the intracellular drug distribution using fluorescence microscopy. First, HeLa cells were incubated in culture medium containing 10 μg / mL drug-loaded micelles SS-GMDP-CPT NPs for 0.5 h, 1 h, 2 h, and 4 h, respectively. Then, cell fluorescence imaging was performed to study the passive targeting ability of SS-GMDP-CPT NPs. Figure 36 As shown, the red and blue fluorescence from the AIE fluorophore DPME and the loaded CPT micelles was mostly retained in the cytoplasm. After 0.5 h of incubation, a weak fluorescence signal was observed in HeLa cells in both channels. After 2 h of incubation, the fluorescence signal was clearly visible in the HeLa cytoplasm, indicating that both CPT and DPME escaped from the micelles and were dispersed in the cells in a free state. When the incubation time was increased to 4 h, a strong fluorescence signal was observed in the HeLa cytoplasm, indicating that more of the tumor drug CPT in the micelles was released into the cells.
[0039] ImageJ software was used to quantify cell imaging scores. For example... Figure 37As shown, after 0.5 h of incubation with SS-GMDP-CPT NPs, the specific fluorescence intensities of blue and red in HeLa cells were 5.42 au and 3.03 au, respectively. After 1 h, the specific fluorescence intensities were 10.88 au and 10.82 au, respectively. After another 4 h of incubation, the specific fluorescence intensities increased to 25.6 au and 23.25 au, respectively. With prolonged incubation, the specific fluorescence intensities began to increase systematically, and the differences in fluorescence intensity became more pronounced. The test results indicate rapid intracellular drug release. Utilizing this unique AIE property, the cellular uptake of polymer micelles can be tracked and monitored intracellularly through the AIE effect in the carrier.
[0040] In summary, this invention utilizes RAFT living polymerization to prepare an amphiphilic triblock polymer SS-GMDP with three disulfide bonds on its side chains, introducing the fluorescent molecule DPME with AIE (Active Injection) properties into the side chains. Then, the drug molecule CPT was successfully encapsulated in PBS medium via self-assembly, yielding polymer nanoparticles SS-GMDP-CPT NPs. SS-GMDP emits orange-red fluorescence near 498 nm, with a fluorescence quantum yield of approximately 12.7% and a fluorescence lifetime of 11.28 ns. Furthermore, SS-GMDP exhibits significant AIE properties in unsuitable solvents, with fluorescence intensity increasing significantly with increasing unsuitable solvent concentration. Simultaneously, the average particle size of the polymer prepared as blank micelles and drug-loaded micelles was 105.71 ± 2.46 nm, while the micelle size increased to 128.53 ± 5.09 nm upon addition of the drug molecule camptothecin (CPT). Moreover, the micelles respond rapidly in high-concentration GSH and acidic environments, opening new possibilities for multifunctional drug delivery systems. Then, in vitro release tests were conducted on the drug-loaded micelles in a simulated tumor environment. The results showed that optimal drug release was achieved under acidic conditions and in the presence of GSH, with a cumulative release of 77.2% over 72 hours. Finally, biological experiments demonstrated that the blank micelles SS-GMDP NPs exhibited low cytotoxicity and good biocompatibility. Compared to the free drug molecule CPT, the drug-loaded micelles SS-GMDP-CPT NPs showed a higher cancer cell mortality rate and a lower hemolysis rate. These test results indicate that this material holds promise as a potential drug delivery carrier. Attached Figure Description
[0041] Figure 1 This is a synthetic route diagram for the triblock copolymer SS-GMDP; Figure 2 This is a schematic diagram illustrating the self-assembly process and drug release of SS-GMDP-CPT NPs. Figure 3 The 1H NMR spectrum of CDPBr; Figure 4 The carbon NMR spectrum of CDPBr; Figure 5 The 1H NMR spectrum of CDPP; Figure 6 The carbon NMR spectrum of CDPP; Figure 7 The 1H NMR spectrum of CDOH; Figure 8 The carbon NMR spectrum of CDOH; Figure 9 The 1H NMR spectrum of DPME; Figure 10 The carbon NMR spectrum of DPME; Figure 11 1H NMR spectrum of SS-GMDP Figure 12 Fourier transform infrared spectrum of SS-GMDP; Figure 13 The gel permeation chromatogram of SS-GMDP; Figure 14 (a, b) Fluorescence emission spectra of SS-GMDP and DPME in different solvents Figure 15 (a, b) Fluorescence spectra and punctuation plots of SS-GMDP in H2O with different volume fractions; (c, d) Fluorescence spectra and punctuation plots of DPME in H2O with different volume fractions; Figure 16 (a, b) Fluorescence spectra and basalt plots of SS-GMDP at different concentrations; (c, d) Fluorescence spectra and basalt plots of DPME at different concentrations; Figure 17 (a, b) Fluorescence spectra and basalt plots of SS-GMDP at different pH values; (c, d) Fluorescence spectra and basalt plots of DPME at different pH values; Figure 18 Fluorescence spectra of SS-GMDP with different concentrations of GSH (0 mM, 1 mM, 5 mM, 10 mM); Figure 19 (a) Changes in SS-GMDP fluorescence spectra at different times; (b) Fluorescence microscopy images of SS-GMDP under continuous irradiation of the red emission channel at 0h, 12h, and 24h. Figure 20 The fluorescence lifetime diagram of SS-GMDP; Figure 21 (a) Particle size variation diagram of SS-GMDP-CPT NPs and SS-GMDP NPs; (b) Particle size distribution diagram of SS-GMDP-CPT NPs; (c) Particle size distribution diagram of SS-GMDP NPs; Figure 22(a, b) SEM and TEM images of SS-GMDP-CPT NPs; (c, d) SEM and TEM images of SS-GMDP NPs; Figure 23 (a) EDS spectrum of SS-GMDP NPs; (b) Elemental composition of SS-GMDP NPs; (c) Surface scans of the five elements C, O, N, S and P in SS-GMDP NPs. Figure 24 (a) Fluorescence spectra of SS-GMDP at different concentrations after the addition of pyrene solution; (b) Intensity ratio (Ig) 365 / I 384 A graph showing the change in logarithm (LgC) of SS-GMDP concentration. Figure 25 (a, b) Particle size changes of SS-GMDP-CPT NPs and SS-GMDP NPs after incubation in PBS (pH=7.4) for 72 h; (c, d) Average particle size changes and line graphs after incubation in PBS (pH=7.4) for 72 h. Figure 26 (a, b) Particle size changes of SS-GMDP-CPT NPs and SS-GMDP NPs after incubation in PBS (pH=6.0) for 12 h; (c, d) Average particle size and change line graph after incubation in PBS (pH=6.0) for 12 h. Figure 27 (a) UV absorbance of SS-GMDP-CPT NPs, SS-GMDP NPs and CPT in DMSO solution; (b) Standard curve of CPT in DMSO solution; Figure 28 The impact of different chain-end ratios of SS-GMDP on DLC and DLE; Figure 29 (a) Bar chart showing the effect of different qualities of SS-GMDP on DLC and DLE; (b) Line chart showing the effect of different qualities of SS-GMDP on DLC and DLE; Figure 30 The in vitro drug release curves of polymer-loaded drug micelles over 72 h are shown in the following environments: pH=6.0+10 mM GSH, pH=7.4+10 mM GSH, pH=7.4, and pH=6.0. Figure 31 The particle size changes of SS-GMDP-CPT NPs after incubation for 72 h at (a) pH=7.4, (b) pH=6.0, (c) pH=7.4+10 mM GSH, and (d) pH=6.0+10 mM GSH. Figure 32SEM images of drug-loaded micelles SS-GMDP-CPT NPs incubated for 72 h at (a) pH=6.0 + 10 mM GSH and (b) pH=7.4 + 10 mM GSH. Figure 33 (a) Hemolysis rate of SS-GMDP-CPT NPs at different concentrations; (b) Images of the hemolysis experiment; Figure 34 MTT cytotoxicity analysis of SS-GMDP NPs at different concentrations after co-incubation with HeLa and MKN-45 cells for 24 h; Figure 35. In vitro cytotoxicity test of SS-GMDP-CPT NPs and CPT at different concentrations after co-incubation with (a, c) HeLa cells and (b, d) MKN-45 cells for 24 h. Figure 36 Fluorescence micrographs of SS-GMDP-CPT NPs incubated with HeLa cells for different time periods (10 μg / mL). Figure 37. Mean fluorescence density of SS-GMDP-CPT NPs in HeLa cells at different time points; Figure 38 shows the 1H NMR spectrum of SS-COOH; Figure 39 shows the carbon NMR spectrum of SS-COOH; Figure 40 shows the 1H NMR spectrum of SS-GPC; Figure 41 shows the carbon NMR spectrum of SS-GPC; Figure 42 shows the 1H NMR spectrum of SS-ME; Figure 43 shows the SS-ME carbon NMR spectrum. Detailed Implementation
[0042] The present invention will be further described below through specific embodiments.
[0043] Example 1 (1) Synthesis of 2-(4-bromophenyl)-3-(4-(diphenylamino)phenyl)acrylonitrile (CDPBr) 4-N,N-diphenylaminobenzaldehyde (5.0 g, 18.30 mmol) was dissolved in 100 mL of anhydrous ethanol and added to a 250 mL three-necked flask. The flask was evacuated and purged three times with N2. p-Bromophenylacetonitrile (4.28 g, 21.96 mmol) and NaOH (0.88 g, 21.96 mmol) were added, and the mixture was stirred at room temperature for 3 h. After the reaction was complete, the product was recrystallized from anhydrous ethanol and dried under vacuum to obtain a yellow solid powder, CDPBr, with a yield of 85%. The 1H and 1C NMR spectra of CDPBr are shown below. Figure 3 , Figure 4 . 1 H NMR (400 MHz, Chloroform-d) δ (ppm): 7.75 (d, 2H), 7.54 (d, 2H), 7.52 (d, 2H), 7.40 (s, 1H), 7.34 (m, 4H), 7.15 (m, 6H), 7.04 (d, 2H). 13 C NMR (151 MHz, Chloroform-d) δ (ppm): 150.21, 146.48, 142.16, 134.25, 132.17, 131.45, 130.77, 127.92, 124.86, 121.15.
[0044] (2) Synthesis of 3-(4-(diphenylamino)phenyl-2-(4-pyridine-phenyl)acrylonitrile (CDPP) CDPBr (1.0 g, 2.22 mmol), pyridine-4-boronic acid (0.33 g, 2.66 mmol), K2CO3 (3.07 g, 22.21 mmol), and tetrakis(triphenylphosphine)palladium (Pd(PPh3)4) (25.41 mg, 0.01 mmol) were added to a 100 mL three-necked flask containing 60 mL THF and 9 mL deionized water. The flask was purged three times under vacuum with N2, heated to reflux at 70 °C for 24 h, cooled to room temperature, and extracted three times with 100 mL DCM. The organic phase was collected, washed with copious amounts of deionized water, dried overnight with anhydrous MgSO4, and the solvent was removed by rotary evaporation. The solution was purified by gradient elution using a: petroleum ether / ethyl acetate (v / v = 15:1) and b: dichloromethane / ethyl acetate (v / v = 2:3) silica gel column chromatography. After vacuum drying, an orange-yellow powder, CDPP, was obtained with a yield of 64%. The 1H and 1C NMR spectra of CDPP are as follows: Figure 5 , Figure 6 . 1 H NMR (400 MHz, Chloroform-d) δ (ppm): 8.70 (s, 2H), 7.79 (m, 2H), 7.73 (m, 2H), 7.65 (d, 1H), 7.54 (m, 4H), 7.30 (m, 6H), 7.14 (m, 6H). 13C NMR (151 MHz, Chloroform-d) δ (ppm): 150.21, 146.48, 142.16, 134.25, 132.17, 131.45, 130.77, 127.92, 124.86, 121.15.
[0045] (3) Synthesis of 3-(4-(diphenylaminophenyl)-2-(4-(1-(2-hydroxyethyl)-1,1,4-pyridin-4-yl)phenyl)acrylonitrile (CDOH) CDPP (2.6 g, 5.8 mmol) was added to a 250 mL three-necked flask, dissolved in 100 mL of chloroform, and purged three times under vacuum with N2. 2-iodoethanol (1.12 g, 6.5 mmol) was added dropwise using a syringe, and the mixture was stirred at room temperature for 72 h. The mixture was extracted three times with 100 mL of saturated saline solution, dried over anhydrous MgSO4 for 12 h, and the solvent was removed by rotary evaporation. Purification was performed by silica gel column chromatography using dichloromethane / methanol (v / v = 10:1) as the eluent. After vacuum drying, a red solid CDOH was obtained, with a yield of 53%. The 1H and 1C NMR spectra of CDOH are shown below. Figure 7 , Figure 8 . 1 H NMR (400 MHz, Chloroform-d) δ (ppm): 8.12 (d, 2H), 7.80 (d, 2H), 7.55 (m, 4H), 7.42 (s, 1H), 7.35 (m, 6H), 7.18 (m, 6H), 7.02 (m, 2H) , 5.92 (s, 1H), 4.60 (t, 2H), 3.95 (t, 2H). 13 C NMR (151 MHz, Chloroform-d) δ (ppm): 160.24, 155.21, 131.22, 129.40, 126.35, 98.18, 64.52, 54.31.
[0046] (4) Synthesis of 4-(4-(1-cyano-2-(4-(diphenylamino)phenyl)vinyl)phenyl)-1-(17-methyl-3,3,54,7,16-trioxo-3,8,15-trioxa-11,12-dithiooctadec-17-en-1-yl)pyridine (DPME) Weigh CDOH (2.46 mmol, 1.22 g), SS-COOH (2.71 mmol, 0.8728 g), dicyclohexylcarbodiimide (DCC) (3.69 mmol, 0.76 g), and 4-dimethylaminopyridine (DMAP) (0.25 mmol, 0.03 g) and dissolve them in 30 mL of anhydrous DCM. Stir at room temperature under N2 for 24 h. After the reaction is complete, filter to remove impurities, remove the solvent by rotary evaporation, and purify by silica gel column chromatography using dichloromethane / methanol (v / v = 10:1) as the eluent to obtain red solid DPME in 48% yield. The 1H and 1C NMR spectra of DPME are shown below. Figure 9 , Figure 10 . 1 H NMR (400 MHz, Chloroform-d) δ (ppm): 8.74 (s, 2H), 7.70 (m, 6H), 7.53 (m, 6H), 7.35 (m, 2H), 7.24 (m, 2H), 7.16 (d, 2H), 7.04 (d, 2H), 6.78(d, 2H), 5.64 (s, 1H),5.42 (s, 1H), 4.72 (d, 2H), 4.45 (d, 2H), 4.22 (m, 4H),3.86 (m, 2H), 3.60 (m, 2H), 3.35 (d, 2H), 3.23 (d, 2H), 2.41 (s, 3H). 13 C NMR (151 MHz, Chloroform-d) δ (ppm): 167.35, 150.12, 147.53,144.25, 141.50, 136.02, 129.06, 127.92, 125.71, 122.04, 99.04, 63.77, 51.84,36.51, 17.92. The synthesis steps of SS-COOH in this process are as follows: ① Synthesis of 2-((2-hydroxyethyl)dithioyl)methacrylate (SS-OH) Weigh 0.75 mL (10 mmol) of 2,2'-dithiodiethanol and 4.2 mL (30 mmol) of triethylamine, and dissolve them in 160 mL of anhydrous tetrahydrofuran (THF) under ice-water bath conditions. The solution is then placed in a 500 mL three-necked flask and stirred at 0 °C for 30 min. Next, 40 mL of THF solution containing 0.75 mL (15 mmol) of methacrylamide chloride is added dropwise, and the mixture is stirred at room temperature for 24 h. The solvent is then removed by rotary evaporation, and the residue is washed with ethyl acetate / petroleum ether (v / v = 1:1). Purification by silica gel column chromatography yields a yellow oily liquid, SS-OH, in 81% yield.
[0047] 1 H NMR (400 MHz, Chloroform-d) δ (ppm): 6.0 (s,1H), 5.5 (s, 1H), 4.4-4.1 (t, 2H), 3.9-3.6 (t, 2H), 3.24 (s, 1H), 3.0-2.6 (dd, 4H), 1.8 (s, 3H). 13 C NMR (151 MHz, Chloroform-d) δ (ppm): 168, 140.48, 126.16, 64.49, 62.12, 41.53, 37.27, 17.92. ② Synthesis of 4-(2-(2-(methacryloyloxy)ethyldithioalkylethoxy)-4-oxobutyric acid (SS-COOH) SS-OH (0.3215 g, 1 mmol), succinic anhydride (0.873 g, 8.73 mmol), and 4-dimethyliminopyridine (DMAP) (1.0665 g, 8.73 mmol) were weighed and dissolved in 30 mL of anhydrous THF. The mixture was stirred at room temperature for 24 h, and the reaction was quenched with 3 mL of water. The mixture was then extracted three times with 40 mL of DCM and three times with 100 mL of saturated NaCl solution. The organic layer was collected, dried overnight with anhydrous MgSO4, and the solvent was removed by rotary evaporation. Finally, the mixture was purified by silica gel column chromatography using ethyl acetate / petroleum ether (v / v = 1:3) as the eluent to obtain a white solid SS-COOH in 72% yield. The 1H and 1C NMR spectra of SS-COOH are shown below. Figure 38 , Figure 39 .
[0048] 1H NMR (400 MHz, Chloroform-d) δ (ppm): 12.3 (s, 1H), 6.0 (s, 1H), 5.7 (s, 1H), 4.4-4.1 (dd, 4H), 3.2-2.6 (dd, 4H), 2.6-2.4 (t, 4H), 2.0-1.7 (s,3H). 13 C NMR (151 MHz, Chloroform-d) δ (ppm): 176.22, 174.48, 166.2, 137.21, 128.12, 37.44, 29.27, 18.02.
[0049] (5) Synthesis of 2-(hydroxymethyl)-17-methyl-4,7,16-trioxy-3,8,15-trioxy-11,12-dithiooctadecyl-17-en-1-yl (2-(trimethylamino)ethyl) phosphate (SS-GPC) Weigh out SS-COOH (0.9661 g, 3 mmol) synthesized in step (4) and dissolve it in 10 mL of DCM. Add N,N'-carbonyldiimidazole (CDI) (0.7297 g, 4.5 mmol) with stirring at room temperature. Dissolve glycerophosphate choline (0.2572 g, 1 mmol) and 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) (0.3045 g, 2 mmol) in 20 mL of dimethyl sulfoxide (DMSO). Stir at 60 °C for 4 h until completely dissolved. After cooling to room temperature, mix the two solutions and stir at room temperature for 24 h. Remove the solvent by gradient elution using petroleum ether, dichloromethane / methanol (v / v=5:1), and methanol / water (v / v=6:1) as eluents. Purify by silica gel column chromatography and freeze-dry to obtain a white solid SS-GPC with a yield of 67%. The 1H and 1C NMR spectra of SS-GPC are as follows: Figure 40 , Figure 41 . 1 H NMR (400 MHz, Chloroform-d) δ (ppm):6.3 (s, 1H), 5.7 (s, 1H), 5.1-4.9 (s, 1H), 4.7-4.5 (s, 2H), 4.4-3.7 (m, 9H), 3.7-3.6 (s, 2H), 3.6-3.4 (s,9H), 3.1-2.9 (d, 4H),2.8-2.6 (t, 2H), 2.5-2.3 (t, 2H), 1.9-1.7 (s, 3H). 13 CNMR(151 MHz, Chloroform-d) δ (ppm): 158.43, 146.32, 140.10, 136.49,113.25,67.35, 61.02, 53.36, 31.21, 26.77, 22.03.
[0050] (6) Synthesis of 2-(azacyclopropane)-1-ethyl(2-((2-(methacryloyloxy)ethyl)dithioyl)succinate (SS-ME) Weigh out SS-COOH (0.3220 g, 1 mmol), N-(2-hydroxyethyl)hexamethylenediamine (0.2860 g, 2 mmol), 4-dimethylaminopyridine DMAP (0.4887 g, 4 mmol), and dicyclohexylcarbodiimide (DCC) (0.4120 g, 0.2 mmol) synthesized in step (4) and dissolve them in 20 mL of DCM. Stir at room temperature for 24 h. After the reaction is complete, extract three times with saturated sodium chloride solution (40 mL), dry with anhydrous MgSO4, remove the solvent by evaporation and rotation, use dichloromethane / methanol (v / v=10:1) as eluent, and purify by silica gel column chromatography to obtain yellow oily liquid SS-ME with a yield of 61%. The 1H and 1C NMR spectra of SS-ME are shown below. Figure 42 , Figure 43 . 1 H NMR (400 MHz, Chloroform-d) δ (ppm): 6.3 (s, 1H), 5.7 (s,1H), 4.5-4.3 (m, 6H), 3.9-3.7 (d, 2H), 3.6-3.4 (t, 4H), 3.1-2.9 (m, 2H), 2.8-2.7 (m,2H), 2.6-2.5 (m, 2H),2.4-2.0 (d, 2H), 1.9-1.5 (m, 4H). 13 C NMR (151 MHz, Chloroform-d) δ (ppm): 176.22, 174.48, 166.2, 137.21, 128.12, 37.44, 29.27, 18.02.
[0051] (7) Preparation of polymer SS-GMDP Weigh out the chain transfer agent 3-((phenylthio)carbonylthio)propionic acid (CADB) (0.0013 g, 0.005 mmol), the initiator azobisisobutyronitrile (AIBN) (0.016 g, 0.1 mmol), and SS-GPC (0.579 g, 1 mmol), and dissolve them in 10 mL of DMF solution. Stir at 80 °C under N2 atmosphere for 12 h, then add SS-ME (0.447 g, 1 mmol) and continue the reaction for another 12 h. Subsequently, add DPME (0.079 g, 0.1 mmol), cool to room temperature, and precipitate with methyl tert-butyl ether. Wash with a large amount of acetone solution. Dialyze the resulting precipitate to deionized water at room temperature for 24 h (MWCO = 3500 Da). Freeze-dry to obtain the polymer SS-GMDP. The 1H NMR spectrum of SS-GMDP is shown below. Figure 11 .
[0052] Example 2 Preparation of polymer-loaded drug micelles and blank micelles Drug-loaded micelles SS-GMDP-CPT NPs were prepared by dialysis. 25 mg of the triblock polymer SS-GMDP and 5 mg of the drug molecule camptothecin (CPT) were weighed and dissolved in 3 mL of DMSO solution. The solution was stirred at room temperature for 3 h, followed by the addition of 10 mL of deionized water and stirring for another 24 h. The solution was then transferred to a dialysis bag (MWCO = 3500 Da) and dialyzed with ultrapure water for 24 h. The ultrapure water was replaced every 3 h for the first 12 h, and then every 6 h thereafter. The final solution was freeze-dried to obtain the drug-loaded micelles SS-GMDP-CPT NPs.
Claims
1. A method for preparing a pH / GSH dual-responsive triblock copolymer with AIE luminescence properties, comprising the following steps: (1) Synthesis of 2-(4-bromophenyl)-3-(4-(diphenylamino)phenyl)acrylonitrile 4-N,N-diphenylaminobenzaldehyde was dissolved in anhydrous ethanol, p-bromophenylacetonitrile and NaOH were added, and the mixture was stirred at room temperature for 2-4 hours under N2 atmosphere. After the reaction was completed, the product was recrystallized from anhydrous ethanol and dried under vacuum to obtain a yellow solid powder CDPBr. (2) Synthesis of 3-(4-(diphenylamino)phenyl-2-(4-pyridine-phenyl)acrylonitrile CDPBr, pyridine-4-boronic acid, K2CO3, and tetrakis(triphenylphosphine)palladium were added to a mixture of THF and deionized water. The mixture was heated under N2 atmosphere and refluxed at 60-80 °C for 24 h. After cooling to room temperature, the mixture was extracted three times with DCM. The organic phase was collected, washed with deionized water, dried overnight with anhydrous MgSO4, the solvent was removed by rotary evaporation, purified by silica gel column chromatography, and dried under vacuum to obtain an orange-yellow powder CDPP. (3) Synthesis of 3-(4-(diphenylaminophenyl)-2-(4-(1-(2-hydroxyethyl)-1,1,4-pyridin-4-yl)phenyl)acrylonitrile CDPP was dissolved in chloroform, 2-iodoethanol was added, and the reaction was stirred at room temperature under N2 atmosphere for 70-75 h. The mixture was extracted three times with saturated brine, dried with anhydrous MgSO4, the solvent was removed by rotary evaporation, purified by silica gel column chromatography, and dried under vacuum to obtain red solid CDOH. (4) Synthesis of 4-(4-(1-cyano-2-(4-(diphenylamino)phenyl)vinyl)phenyl)-1-(17-methyl-3,3,5-trioxa-8,15-dithiaheptadec-16-en-1-yl)pyridine-1-onium iodide CDOH, 4-(2-(2-(methacryloyloxy)ethyldithioalkylethoxy)-4-oxobutyric acid, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine were dissolved in anhydrous DCM and stirred at room temperature under N2 for 20-25 h. After the reaction was completed, the mixture was filtered to remove impurities, the solvent was removed by rotary evaporation, and the mixture was purified by silica gel column chromatography to obtain red solid DPME. (5) Synthesis of 2-(hydroxymethyl)-17-methyl-4,7,16-trioxy-11,12-dithiooctadecyl-17-en-1-yl (2-(trimethylamino)ethyl) phosphate 4-(2-(2-(methacryloyloxy)ethyldithioalkylethoxy)-4-oxobutyric acid was dissolved in DCM, and N,N'-carbonyldiimidazole was added with stirring at room temperature. Glyceryl phosphate choline and 1,8-diazabicyclo[5.4.0]undec-7-ene were dissolved in dimethyl sulfoxide and stirred at 55-65°C for 3-5 h until completely dissolved. After cooling to room temperature, the two solutions were mixed and stirred at room temperature for 20-25 h. The solution was purified by silica gel column chromatography and freeze-dried to obtain a white solid SS-GPC. (6) Synthesis of ethyl 2-(azacyclopropane)-1-ethyl(2-((2-(methacryloyloxy)ethyl)dithioyl)succinate Weigh out 4-(2-(2-(methacryloyloxy)ethyldithioalkylethoxy)-4-oxobutyric acid, N-(2-hydroxyethyl)hexamethylenediamine, 4-dimethylaminopyridine, and dicyclohexylcarbodiimide and dissolve them in DCM. Stir at room temperature for 20-25 h. After the reaction is complete, extract with saturated sodium chloride solution, dry with anhydrous MgSO4, remove solvent by evaporation and rotation, and purify by silica gel column chromatography to obtain SS-ME. (7) Preparation of polymer SS-GMDP Chain transfer agent CADB, initiator azobisisobutyronitrile (AIBN), and SS-GPC were dissolved in DMF solution and stirred at 75–85 °C for 10–15 h under N2 atmosphere. SS-ME was added and the reaction continued for another 10–15 h. Subsequently, DPME was added, and after cooling to room temperature, methyl tert-butyl ether precipitated. The precipitate was washed with acetone solution, dialyzed with deionized water at room temperature, and freeze-dried to obtain polymer SS-GMDP.
2. The method for preparing the pH / GSH dual-responsive triblock copolymer with AIE luminescence properties according to claim 1, characterized in that: In step (1), the molar ratio of 4-N,N-diphenylaminobenzaldehyde to p-bromophenylacetonitrile is 1:1 to 1:5; the molar ratio of p-bromophenylacetonitrile to NaOH is 1:1 to 1:
2.
3. The method for preparing the pH / GSH dual-responsive triblock copolymer with AIE luminescence properties according to claim 1, characterized in that: In step (2), the molar ratio of CDPBr to pyridine-4-boronic acid is 1:1 to 1:1.5; the molar ratio of CDPBr to K2CO3 is 1:10 to 1:11; and the molar ratio of tetrakis(triphenylphosphine)palladium to CDPBr is 1:
222.
4. The method for preparing the pH / GSH dual-responsive triblock copolymer with AIE luminescence properties according to claim 1, characterized in that: In step (3), the molar ratio of CDPP to 2-iodoethanol is 1:1 to 1:1.
5.
5. The method for preparing the pH / GSH dual-responsive triblock copolymer with AIE luminescence properties according to claim 1, characterized in that: In step (4), the molar ratio of CDOH to 4-(2-(2-(methacryloyloxy)ethyldithioalkylethoxy)-4-oxobutyric acid is 1:1 to 1:1.5; the molar ratio of CDOH to dicyclohexylcarbodiimide is 1:1.2 to 1:1.6; and the molar ratio of 4-dimethylaminopyridine to CDOH is 1:8 to 1:
10.
6. The method for preparing the pH / GSH dual-responsive triblock copolymer with AIE luminescence properties according to claim 1, characterized in that: In step (5), the molar ratio of 4-(2-(2-(methacryloyloxy)ethyldithioalkylethoxy)-4-oxobutyric acid to N,N'-carbonyldiimidazole is 1:1 to 1:2; the molar ratio of glycerophosphate choline to 1,8-diazabicyclo[5.4.0]undec-7-ene is 1:1 to 1:2; and the molar ratio of N,N'-carbonyldiimidazole to 1,8-diazabicyclo[5.4.0]undec-7-ene is 2:1 to 3:
1.
7. The method for preparing the pH / GSH dual-responsive triblock copolymer with AIE luminescence properties according to claim 1, characterized in that: In step (6), the molar ratio of 4-(2-(2-(methacryloyloxy)ethyldithioalkylethoxy)-4-oxobutyric acid to N-(2-hydroxyethyl)hexamethylenediamine is 1:1 to 1:2; the molar ratio of N-(2-hydroxyethyl)hexamethylenediamine to 4-dimethylaminopyridine is 1:1 to 1:2; and the molar ratio of N-(2-hydroxyethyl)hexamethylenediamine to dicyclohexylcarbodiimide is 8:1 to 12:
1.
8. The method for preparing the pH / GSH dual-responsive triblock copolymer with AIE luminescence properties according to claim 1, characterized in that: In step (7), the molar ratio of CADB to DPME is 1:18 to 1:22; the molar ratio of azobisisobutyronitrile to DPME is 1:1 to 1:2; the molar ratio of DPME to SS-GPC is 1:8 to 1:12; and the molar ratio of DPME to SS-ME is 1:8 to 1:
12.
9. The application of the pH / GSH dual-responsive triblock copolymer prepared by the method according to claim 1 in the preparation of drug carriers.
10. The application of the pH / GSH dual-responsive triblock copolymer according to claim 9 in the preparation of drug carriers, characterized in that: The triblock copolymer loads the drug molecule camptothecin through self-assembly. The triblock polymer SS-GMDP and the drug molecule camptothecin are dissolved in DMSO solution and stirred at room temperature for 2-4 h. Then deionized water is added and stirring is continued for 20-25 h. The mixture is dialyzed with ultrapure water and the final solution is freeze-dried to obtain drug-loaded micelles SS-GMDP-CPT NPs.
Citation Information
Patent Citations
Polymers and oligomers with aggregation-induced emission characteristics for imaging and image-guided therapy
CN106470964A
Polymeric drug carrier with oxidation reduction response and AIE (aggregation-induced luminescence) effect, polymeric drug-loaded micelle and preparation methods thereof
CN108559040A